Efeito de filtros ópticos na função visual de espeleologistas - Monteiro, Nádia (2015)
Speleologist’s perform their activity in demanding visual conditions of very low luminance - many visual tasks involve resolution of detail under conditions of low contrast. Work related conditions in a cave as exposure to heat, chemicals, dust and poor lighting conditions could influence the integrity of the visual system and predispose the eye to diseases that eventually affect vision. Poor lighting conditions cause a variety of symptoms of visual discomfort and may increase the risk of accidents. Good visual acuity is crucial for several and has an important role for safety purposes. The aim of this study was to evaluate lighting conditions and optical filters effects on visual performance in speleologists exposed to cave environments.